The use of different adhesive filling material and mass combinations to restore class II cavities under loading and shrinkage effects: a 3D-FEA. Issue 5 (6th July 2021) - Ausiello, P.; Ciaramella, S.; De Benedictis, A.; Lanzotti, A.; Tribst, J. P. M.; Watts, D. C.
Abstract: 3D tooth models were virtually restored: flowable composite resin + bulk-fill composite (A), glass ionomer cement + bulk-fill composite (B) or adhesive + bulk-fill composite (C). Polymerization shrinkage and masticatory loads were simulated. All models exhibited the highest stress concentration at the enamel–restoration interfaces. A and C showed similar pattern with lower magnitude in A in comparison to C. B showed lower stress in dentine and C the highest cusps displacement. The use of glass ionomer cement or flowable composite resin in combination with a bulk-fill composite improved the biomechanical behavior of deep class II MO cavities.